2020
DOI: 10.3390/antiox9111150
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Heme Oxygenase-1 in Aneurysmal Diseases

Abstract: Abdominal aortic aneurysm (AAA) and intracranial aneurysm (IA) are serious arterial diseases in the aorta and brain, respectively. AAA and IA are associated with old age in males and females, respectively, and if rupture occurs, they carry high morbidity and mortality. Aneurysmal subarachnoid hemorrhage (SAH) due to IA rupture has a high rate of complication and fatality. Despite these severe clinical outcomes, preventing or treating these devastating diseases remains an unmet medical need. Inflammation and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 153 publications
0
9
0
Order By: Relevance
“…Currently, some studies have investigated novel treatment options based on the inflammatory response in aortic dissection. HOMX1 has been demonstrated to be a protective factor in cardiovascular health, and excessive vascular inflammation has been observed in HOMX1-deficient humans (58)(59)(60). Ho et al investigated the role of HOMX-1 in angiotensin IIinduced AAA formation in HO-1+/+apoE-/-and HO-1-/-apoE-/-mice and demonstrated the essential roles of HOMX-1 in suppressing the pathogenesis of abdominal aortic aneurysm (61).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some studies have investigated novel treatment options based on the inflammatory response in aortic dissection. HOMX1 has been demonstrated to be a protective factor in cardiovascular health, and excessive vascular inflammation has been observed in HOMX1-deficient humans (58)(59)(60). Ho et al investigated the role of HOMX-1 in angiotensin IIinduced AAA formation in HO-1+/+apoE-/-and HO-1-/-apoE-/-mice and demonstrated the essential roles of HOMX-1 in suppressing the pathogenesis of abdominal aortic aneurysm (61).…”
Section: Discussionmentioning
confidence: 99%
“…Both models suggest that lack of HO-1 exacerbates AAA formation. In accordance, the relevance of HO-1 in AAA biology was addressed using HO-1 modulators, and the HO-1 upregulation was concomitant with a positive impact on AAA [reviewed in [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of such modifications disrupts the aortic wall, making the aorta vulnerable to hemodynamic injury [ 23 , 24 ]. Apart from mutations in the fibrillin-1 gene, also changes within transforming growth factor 尾 receptor 2 (TGF-尾R2) and TGF-尾R1, which regulate extracellular matrix synthesis and homeostasis, can cause Marfan鈥檚 syndrome [ 25 , 26 , 27 ]. According to estimations, up to 5% of MFS patients are carriers of the mutation in the TGF-尾R2 gene [ 28 ].…”
Section: Marfan鈥檚 Syndrome (Mfs)mentioning
confidence: 99%
“…Recently, some studies have suggested the protective function of heme oxygenase-1 (HO-1) in the abdominal aortic aneurysm (AAA). Heme oxygenase-1 is a stress response protein that plays an essential role in the protection against injury since it possesses antioxidative and anti-inflammatory properties [ 27 ]. Its utility has been previously studied in cardiovascular diseases [ 126 , 127 ].…”
Section: Oxidative Stress-reducing Strategiesmentioning
confidence: 99%
See 1 more Smart Citation